Gauging the impact of a low-interest rate environment on German life insurers - Anke Kablau; Michael Wedow (Deutsche Bundesbank, 2011)
A low interest rate environment can pose a key risk to the life insurance sector. A deteriorating return on investment holdings jeopardizes the guaranteed return on life insurance contracts. In this paper, we examine the effect of low interest rates on German life insurers by applying various adverse scenarios to a simple model of life insurers' balance sheets. A low return on investment can lead to a depletion of the bonus and rebate provisions. As a result, life insurers resilience may deteriorate. By way of this analysis, we can model approximately when the bonus and rebate provisions will be depleted.
Keywords: G14; G21; G28; 330; Life insurance; low-interest rate environment; financial stability